Pronounced neonatal breast enlargement beyond the first week of life and its regression correlates with serum prolactin levels: a case series - Bartos, Hilda-Brigitta; Weise, Linnéa; Schock, Alexandra; Diez, Sonja; Weiß, Christel; Drommelschmidt, Karla; Mahnken, Andreas H.; Hummler, Helmut; Müller, Hanna (The journal of pediatric endocrinology and metabolism, 2024)
Objectives Mild breast swelling is frequently observed in newborns during the first postnatal week. Breast enlargement is also observed in a minor proportion of infants beyond the first postnatal week, leading to discussions how to deal with it. Our objective was to review a case series of infants with prolonged breast swelling. Case presentation We examined five infants with pronounced breast enlargement beyond the first postnatal week and measured human chorionic gonadotropin (HCG), estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and progesterone (P4) in blood samples and analyzed breast volume by sonographic volume determination in all infants initially and across time. The regression of breast enlargement positively correlated with serum prolactin levels in infants with breast enlargement beyond the first week of life. Complete regression occurred after several weeks and was characterized by normalization of serum prolactin levels. Conclusions The present study emphasizes the role of prolactin in neonates with pronounced breast enlargement beyond the first week of life.
Online veröffentlicht: 13. August 2024
Gesehen am 04.11.2024